A Comparative Investigation on the Metaphors in Chinese and American Mainstream Media (LSP International Journal, 2023)
Since COVID-19 outbreak in December 2019, there is a “narrative battle” between China and the US. Through rhetorical devices, such as metaphors, mainstream media plays a significant role in society in shaping public opinions. Although scholars have started to explore the metaphors employed between Chinese and American media during the pandemic, there is less information about a systematic comparative study on the COVID-19 related metaphors in Chinese and American media. This study provides a comparison of the metaphors in the COVID-19 editorials in the China Daily (CD) and the New York Times (NYT) through grounded theory. In general, it determines CD employs more metaphors than that in the NYT. In addition, the employment of war metaphor in NYT to describe the coronavirus is way more less than that in CD. Also, both CD and NYT tries to envoke the public through the employment of impressive historical issues.